Evaluating intimal hyperplasia under clinical conditions. (30th March 2018) - Mylonaki, Ioanna; Allain, Elisabeth; Strano, Francesco; Allémann, Eric; Corpataux, Jean-Marc; Meda, Paolo; Jordan, Olivier; Delie, Florence; Rougemont, Anne-Laure; Haefliger, Jacques-Antoine; Saucy, François
Abstract: OBJECTIVES: Open arterial revascularization using venous segments is frequently associated with the development of intimal hyperplasia (IH), leading to severe restenosis and graft failure. The lack of treatment to prevent this pathology is a major problem. Therefore, we generated a new porcine model, which closely mimics the clinical development of human IH, to test the therapeutic potential of candidate drugs. METHODS: A patch of jugular vein was sutured to the right common carotid artery of pigs, to expose the vein to haemodynamic conditions of the arterial bed. Four weeks after surgery, the operated vessels which received no further treatment (the control group) were compared with (i) contralateral, non-operated vessels (the healthy group); (ii) vessels of pigs that received a perivascular application of a drug-free microparticle gel (the placebo group) and (iii) vessels of pigs that perioperatively received the same gel loaded with 10-mg atorvastatin (the atorvastatin group). RESULTS: When compared with non-operated vessels, all operated segments displayed a sizable IH which was thicker in the venous patch than in the host artery. These alterations were associated with a thickening of the intima layer of both vessels in the absence of inflammation. The intima/media ratio has been significantly increased by 2000-fold in the vein patches. Perivascular application of atorvastatin did not prevent IH formation. However, the drug increased the adventitial neovascularization in the operated vessels. CONCLUSIONS: The novel porcine model allows for monitoring IH formation under haemodynamic conditions which mimic clinical situations. It should facilitate the screening of innovative treatments to prevent restenosis.